PENGARUH EMOTIONAL BRANDING, NILAI PELANGGAN DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN J.CO JAVA MALL SEMARANG - Gunung Setiadi; Handoyo Djoko Waluyo; Ngatno Ngatno (Universitas Diponegoro, 2015)
Changes in Indonesian lifestyles become modern required to act more quickly and dynamically, making people liked everything instant case, as well as the lifestyle of the people in choosing foods. One of fast-food restaurant in Indonesia is J.CO Donuts & Coffee. J.CO Donuts & Coffee Java Mall Semarang is one thriving restaurant in Semarang, but the sales turnover fluctuated during January to December 2014, accompanied by the rise and fall of the number of visitors.This study aims to determine the effect of emotional branding, customer value and brand image to customer loyalty through customer satisfaction J.CO Donuts & Coffee Java Mall Semarang. Type of research is used explanatory. The population in this study are customers J.CO Donuts & Coffee Java Mall Semarang, by using the theory of Cooper and Emory then taken 100 respondents to be sampled and the sampling technique used a combination of accidental sampling and purposive sampling. Methods of data collection using questionnaires, interviews, and documentation. Measurement scale used a Likert scale. The data analysis used validity test, reliability test, correlation coefficient, analysis of simple and multiple linear regression, determinant coefficient, significance test (t test and F test) and Sobel test with SPSS.The study concludes that emotional branding, customer value and brand image together (simultaneously) or partially affect the dependent variable of customer satisfaction and customer loyalty. Based on the results of Sobel test, the direct effect of emotional branding on customer loyalty greater than the indirect effect, the direct effect of customers value on customer loyalty greater than the indirect effect , nor the direct effect of brand image on customer loyalty greater than the indirect effect.Suggestions in this study that J.CO Donuts & Coffee Java Mall Semarang must add their promotional media, and J.CO should be able to make their website more interactive site to make it more attractive. Furthermore J.CO need to review the price is set to be more economical. And should J.CO start making a new product or a new formula that can deliver more benefits for consumers from consuming the products J.CO. And to increase customer loyalty, could be done by giving promotions or discounts.